VD_FINDINFO Jug / 2010 / 68 vom 11. August 2010 - VD Tribunal cantonal (2010)
PRÉVOYANCE PROFESSIONNELLE SELON LA LPP, ACTION EN PARTAGE | 122 CC, 123 CC, 141 CC, 142 CC, 22 al. 1 LFLP, 22 al. 2 LFLP, 22 LFLP